Spheroidization and Coarsening of Eutectic Si Particles in Al-Si-Based Alloys - Mohamed Ibrahim; Mohamed Abdelaziz; Agnes Samuel; Herbert Doty; Fawzy Samuel (Advances in Materials Science and Engineering)
The present study was carried out on three Al-Si cast alloys viz., 319, 356, and 413 alloys, solidified at 8°C/s. Samples from 319 and 413 alloys were solution heat-treated at 510°C, whereas samples from 356 alloy were solutionized at 550°C, for up to 1200 h. The results reveal that complete spheroidization of eutectic Si particles in terms of achieving individual spherical particles cannot be achieved in most Al-Si-Cu-Mg alloys even after a solutionizing time of 1200 h which contradicts with the existing theory. Addition of Sr to Cu-free 356 alloy could lead to complete spheroidization after 1200 h at 550°C if the alloy was solidified at 8°C/s. Besides the dissolution theory of Ostwald, coarsening of Si particles can as well take place by impingement, fusion, and agglomeration. Increasing the Si content makes it difficult to achieve spheroidization, i.e., fragmentation and coarsening. Results obtained from observations of deeply etched samples (3D) contradict those obtained from polished samples (2D).